Gangguan tidur dan risiko obesitas sentral pada laki-laki dewasa di Indonesia: suatu kajian analisis data Indonesian family life survey 5 - Listhia Hardiati Rahman; Lientje Setyawati Maurits; Susetyowati Susetyowati (Berita Kedokteran Masyarakat (BKM), 2019)
Sleep disturbances and risk of central obesity for male adults in Indonesia (analysis data Indonesian Family Life Survey/IFLS 5)Purpose: This study aimed to analyze the role of sleep disturbances for central obesity in Indonesia.Methods: This type of research is observational with a cross-sectional design. The study used secondary data from the Indonesia Family Life Survey (IFLS) 5 in 2014-2015. Bivariate, multivariate logistic regression, and chi-square were used for statistical analysis. Results: At the end of the study, the results showed no association between sleep disturbances and the risk of central obesity (p=0.54). The significant relationship of central obesity was found in physical activity and smoking habits, but not significant in the consumption of fast food.Conclusions: Sleep disturbance does not have a significant relationship with the risk of central obesity. Although not showing a significant relationship, have a good sleep quality may protect against obesity risk.